2013
DOI: 10.1007/978-3-7091-1434-6_49
|View full text |Cite
|
Sign up to set email alerts
|

Early Cerebral Circulation Disturbance in Patients Suffering from Different Types of Severe Traumatic Brain Injury: A Xenon CT and Perfusion CT Study

Abstract: Moderate hypothermia therapy, which decreases CBF, the cerebral metabolic rate oxygen consumption (CMRO2), and intracranial pressure might be effective against the types of TBI accompanied by cerebral circulation disturbance. We have to use all possible measures including hypothermia therapy to treat severe TBI patients according to the type of TBI that they have suffered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Identifying cases of TBI where the use of hypothermia is warranted is vital. In agreement with previously mentioned data, xenon- and perfusion-CT analyses demonstrated disturbances in cerebral blood flow (CBF) in TBI patients [53]. In that study, Honda et al .…”
Section: Prophylactic Hypothermia and Hyperbaric Oxygen Therapy (Hbot)supporting
confidence: 89%
See 1 more Smart Citation
“…Identifying cases of TBI where the use of hypothermia is warranted is vital. In agreement with previously mentioned data, xenon- and perfusion-CT analyses demonstrated disturbances in cerebral blood flow (CBF) in TBI patients [53]. In that study, Honda et al .…”
Section: Prophylactic Hypothermia and Hyperbaric Oxygen Therapy (Hbot)supporting
confidence: 89%
“…In that study, Honda et al . (2013) found CBF in focal TBI patients to be more perturbed than in diffuse TBI [53]. The research group suggested moderate hypothermia should be used in managing cases of TBI involving larger CBF changes.…”
Section: Prophylactic Hypothermia and Hyperbaric Oxygen Therapy (Hbot)mentioning
confidence: 99%
“…that do not reach ischemic levels. 225,226 However, after TBI, metabolic/hemodynamic requirements of the tissue may differ from normal tissues and could potentially participate in both the acute and more chronic consequences of neurotrauma. 227 In addition to alterations in blood flow, changes in vascular reactivity to various stimuli, including vasodilators, have also been emphasized in the literature.…”
Section: Cerebral Blood Flow Alterationsmentioning
confidence: 99%
“…Furthermore, CBF can be calculated either by a non-deconvolution or a deconvolution algorithm, of which the latter is less prone to error and was preferred (229). There are several studies validating and standardising the results of CTP based measurements of CBV and CBF (229) and showing adequate correlation between CBF calculations derived from CTP and Xe-CT (230,231), thus the CBF data was pooled before statistical analysis.…”
Section: Perfusion Computed Tomographymentioning
confidence: 99%
“…Although above ischemic thresholds, CBF was lower than normal, plausibly due to an effect of sedation used in the majority of patients (11/12) at time of CBF evaluation. The use of two different methods for determining CBF can be criticised, although there are studies showing reliable translation of CBF between Xe-CT and CTP (230,231,262). Failure to utilise CTP would exclude all extubated patients from the study protocol, since Xe-CT requires sedation and mechanical ventilation.…”
Section: Metabolic Crisis In Perihaemorrhagic Zone (Paper I)mentioning
confidence: 99%